Kepemimpinan Kepala Sekolah Perempuan di Sekolah Dasar Muhammadiyah Kabupaten Sleman: Female Principal Leadership at Muhammadiyah Elementary School, Sleman Regency - Widodo, Hendro (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine conceptual skills, human relationship skills and technical skills of female school principals in improving the performance of Muhammadiyah elementary school teachers throughout Sleman Regency. The research approach used in this study is a qualitative approach. The determination of the research subject was done by purposive sampling technique. Data collection techniques were carried out using interviews, observation, questionnaires and documentation. The results of the study concluded that the conceptual skills of female principals in Muhammadiyah Elementary School, Sleman Regency included in very good categories (87%). Similarly humanitarian skills are in the very good category (84%). While technical skills are in good category (77%). This means that the technical skills of female principals in Muhammadiyah Elementary School in Sleman Regency are lower than the conceptual skills and humanitarian skills.